External Validity of the Indonesian Wechsler Adult Intelligence Scale – Fourth Edition (WAIS-IV-ID) - Christiany Suwartono; Lidia L. Hidajat; Magdalena S. Halim; Marc P. H. Hendriks; Roy P. C. Kessels (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
In this research, we investigated the external validity of WAIS-IV-ID using other intelligence tests and educational achievement as criteria. We had 194 participants in total. The results showed the Full-Scale IQ score (FSIQ) of the WAIS-IV-ID had moderate yet significant correlation with three intelligence tests, namely Standard Progressive Matrices (SPM, n = 194), Cattell’s Culture Fair Intelligence Test (CFIT, n = 134), and the Wechsler-Bellevue Intelligence Scale (WBIS, n = 44). There was also a significant positive correlation between the FSIQ and educational achievement score, the Grade Point Average (GPA, n = 51). The four indexes of the WAIS-IV-ID had a significant positive correlation with the SPM, CFIT, and WBIS, except for Verbal Comprehension Index (VCI). We found significant correlations between full-scale IQ with GPA. For the index score, we found significant correlations between Processing Speed Index (PSI) with GPA. We conclude that the WAIS-IV-ID is valid externally.